2018
DOI: 10.1108/cms-03-2018-0448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of benevolent leadership on follower taking charge

Abstract: Purpose The topic of employees’ taking charge behaviors has garnered increasing interest in both practical and academic fields. Leaders play a critical role in influencing followers’ taking charge behaviors, yet few studies have explored the predicting role of benevolent leadership. Drawing from proactive motivation literature, this paper aims to investigate a moderated mediation model that examines work engagement as the mediator and role-breadth self-efficacy as the moderator in the relationship between bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Other studies have shown that empowered and ethical leaders do not have a significant direct impact on employees' taking-charge behavior (Lee, 2016;Qian et al, 2018). Xu et al (2018) also examined the impact of benevolent leadership on employees' proactive change behavior. In contrast, Ouyang et al (2015) found that there is a negative relationship between abusive supervision and proactive behavior because the style of leadership reduces subordinates' perceived insider status within an organization.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that empowered and ethical leaders do not have a significant direct impact on employees' taking-charge behavior (Lee, 2016;Qian et al, 2018). Xu et al (2018) also examined the impact of benevolent leadership on employees' proactive change behavior. In contrast, Ouyang et al (2015) found that there is a negative relationship between abusive supervision and proactive behavior because the style of leadership reduces subordinates' perceived insider status within an organization.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Our findings mainly reveal the positive impact of inclusive leadership on taking-charge behavior. Thus, in response to the call for more context models to reveal the relationship between leadership and taking-charge behavior (Xu et al, 2018), this study expanded existing research at the organizational level and provided an application context. Second, based on SDT and social information processing theory, the variables mediating employees' psychological safety and thriving at work were examined.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other proactive behaviors, such as individual innovation, voice, and organizational citizenship behaviors (Bies, 1988;Scott and Bruce, 1994;Walumbwa et al, 2012), taking charge has characteristics of being change oriented, risky, and proactive (Morrison and Phelps, 1999;Mcallister et al, 2007). Therefore, whether subordinates take part in taking charge relies on the form of leadership and managerial practices in organizations (Crant, 2000;Ning et al, 2013;Li et al, 2015;Xu et al, 2018).…”
Section: Social Exchange and Subordinate Taking Chargementioning
confidence: 99%
“…For example, Zhao et al (2016) argued that transformational leaders are people who have the ability to touch the hearts of their subordinates. Transformational leaders are always encouraging leaders, capable of delivering and setting standards of behavior that can be emulated by subordinates (Wu, 2017;Xu et al, 2018). Burn (1978), the founder of the concept of transformational leadership, has set transformational leadership as "a mutual stimulus that transforms followers into leaders and can transform leaders into moral agents."…”
Section: Theoretical Background and Research Frameworkmentioning
confidence: 99%